Kajian Literatur: Metode Mind Mapping Pada Mata Pelajaran Pendidikan Agama Islam - Anisah Prihatini, Laura; Maulana Jamaludin, Gilang (Departement of PAI, Universitas Majalengka, 2024)
This article aims to examine the mind mapping method in Islamic Religious Education subjects, which is motivated by the fact that students' failure to get good grades at school must be seen from many factors, such as students' basic abilities, facilities and infrastructure, teacher professionalism, effectiveness, etc. One of the bases used by educators to organize learning process activities is learning methods. The development of increasingly advanced times is accompanied by increasingly diverse learning methods, including the mind mapping learning method. The data used in this research is secondary data originating from the results of previous research, not direct experience, namely scientific journals that have been published. There are 15 national journals that match this research variable which were published in 2018-2023.